Examining of Issues on Flood Disaster Management in Malaysia - Shazwani Shafiai; Mohamad Sukeri Khalid (International Review of Management and Marketing, 2016)
Flooding in Malaysia has made various impacts to the victims in terms of damage to property and loss of life. Besides that, the victims also suffer after flood disaster occur. Because of that, the purpose of this paper is to describe the issues and problem of disaster relief management provided by government to the victims in Malaysia for phases during and post-disaster caused by flooding. Presently, the disaster management in Malaysia including flood almost based on top-down approach that was predominantly an official strategy from Directive No. 20 by National Security Council (MKN) of Malaysia. These instructions outline has set the role and responsibilities of the agencies involved and also covers the action of monitoring the activities in disaster management. Therefore, this paper presents findings from the literature review by previous research in this topic. The result show that, in Malaysia, a study concerning the evaluation of the effectiveness policy implementation at levels during and post-disaster that affect the flood victims were poorly implemented. Further to that, this paper will attempt to describe the issues of disaster relief management for phases during and post-disaster that has been criticized by previous researchers.